A JURIDICAL REVIEW OF INFORMED CONSENT BASED ON LAW NUMBER 17 OF 2023 CONCERNING HEALTH AS A REPLACEMENT FOR LAW NUMBER 36 OF 2009 - Kurniawan, Franky; Aspan, Hendry; Andoko (Universitas Bengkulu, 2024)
In contemporary times, with the increasing legal awareness among the general public, the aspect of legal protection has become a focal point in the healthcare legal framework in Indonesia. The Law Number 17 of 2023 concerning Health, replacing Law Number 36 of 2009, illustrates significant changes in the healthcare legal structure in Indonesia. One of the primaries focuses in the implementation of this law is informed consent, which serves as a legal protection tool for patients. Therefore, this study aims to explore the regulation of informed consent in Law Number 17 of 2023 and its implementation among healthcare professionals or facilities. This research employs a normative juridical analysis method by examining the document of the Republic of Indonesia Law Number 17 of 2023 concerning Health, which replaces Law Number 36 of 2009 concerning Health. Legal reviews are conducted by referring to various legal sources and expert opinions. The research findings indicate that Law Number 17 of 2023 establishes a stronger foundation compared to the previous law for the implementation of informed consent. Informed consent is emphasized as both a medical duty and a patient's right, with an emphasis on providing comprehensive information. These changes reflect responses to the unequal access to healthcare services and the need to strengthen the national healthcare system, particularly in the context of emergencies, extraordinary events, or outbreaks. The study notes that there is still a need for adaptation and thorough understanding from healthcare professionals and facilities to maintain a balance between patient rights and the public health interest. Further issues to be addressed include aspects of informed consent that are not elaborated in detail in this new law, such as medical expansion procedures and decisions regarding life-sustaining treatment cessation or postponement. Keywords: Healthcare Law; Informed Consent; Legal protection.